Extinction risk assessment of Brazilian Bonamia (Convolvulaceae) - Kojima, Roberta Keyla; Moreira, André Luiz Da Costa; Simões, Ana Rita Giraldes; Amorim, Eduardo Toledo De; Simão-Bianchini, Rosângela (Phytotaxa, 2026)
This study assessed the extinction risk of Bonamia in Brazil based on IUCN criteria. Taxonomic data were consolidated from “Flora e Funga do Brasil”, considering only accepted names. Records from online databases and non-digitized herbaria were cross-referenced, totaling 612 reliable entries. Biological information was gathered from specialized literature, field data, and supplementary sources. The analysis followed IUCN guidelines using the “Proflora” platform. Of the 17 species assessed, six were classified as threatened, with the Cerrado being the most critical region due to agricultural expansion. Data gaps remain, especially in the northern Cerrado and the Caatinga, indicating the need for further research to ensure effective conservation.